Postoperative myopic shift and visual acuity rehabilitation in patients with bilateral congenital cataracts - Lin, Duoru; Zhu, Qiaolin; Zhang, Shuyi; Zhou, Fengqi; Zhao, Lanqin; Wang, Qiwei; Chen, Wan; Chen, Hui; Lin, Xiaoshan; Feng, Huanling; Zhong, Qiuping; Chen, Jingjing; et al. (Frontiers in Medicine, 2024)
Background This study aimed to explore the postoperative myopic shift and its relationship to visual acuity rehabilitation in patients with bilateral congenital cataracts (CCs). Methods Bilateral CC patients who underwent cataract extraction and primary intraocular lens implantations before 6 years old were included and divided into five groups according to surgical ages (<2, 2–3, 3–4, 4–5, and 5–6 years). The postoperative myopic shift rates, spherical equivalents (SEs), and the best corrected visual acuity (BCVA) were measured and analyzed. Results A total of 1,137 refractive measurements from 234 patients were included, with a mean follow-up period of 34 months. The postoperative mean SEs at each follow-up in the five groups were linearly fitted with a mean R2 = 0.93 ± 0.03, which showed a downtrend of SE with age (linear regression). Among patients with a follow-up of 4 years, the mean postoperative myopic shift rate was 0.84, 0.81, 0.68, 0.24, and 0.28 diopters per year (D/y) in the five age groups (from young to old), respectively. The BCVA of those with a surgical age of <2 years at the 4-year visit was 0.26 (LogMAR), and the mean postoperative myopic shift rate was 0.84 D/y. For patients with a surgical age of 2–6 years, a poorer BCVA at the 4-year visit was found in those with higher postoperative myopic shift rates (r = 0.974, p = 0.026, Pearson’s correlation test). Conclusion Performing cataract surgery for patients before 2 years old and decreasing the postoperative myopic shift rates for those with a surgical age of 2–6 years may benefit visual acuity rehabilitation.